Grounding financialisation: Development, inclusion, and agency. Issue 2 (1st July 2021) - Banks, Glenn; Overton, John
Abstract: The increasing complexity and visibility of financial capital and processes in the global economy and in everyday lives offers both tantalising promise and pitfalls. This review of financialisation in global development develops three key themes: debates and contests over the definition, nature, and extent of financialisation ("what is it"); the erosion within these debates of distinctions between long‐held categories within development – between intentional and immanent, or "big D" and "little d" development, for example; and an exploration of how financialisation has drawn attention to more complex understandings and analyses of risk and its implications for the global economy and everyday lives in the Global South. Drawing on material from the Pacific and situating this alongside existing literature, this review uses these themes to argue that while there is much that is new in the nuance of these processes, there is nothing inherently emancipatory in the new technologies of financialisation. And the often heralded "democratisation of finance" that it represents often serves to extend the reach of capitalism and ties individuals, households, and communities more tightly into the global circuits and structures of capital. These processes themselves though are rarely uncontested, and the plethora of forms they assume reflect localised conditions, geographies, and forms of agency. Abstract : Development and aid are being increasingly financialised as new financial institutions and products permeate into the developments sector. This process has profound implications for the way we understand new configurations of development and the way risk is reconstituted as a financial commodity.